Evidence of Girik Documentation in Land Acquisition Disputes (Study of Tangerang District Court Decision Number 907/Pdt. G/2018/PN Tng) - Adhelia Puspa Rini; Atik Winanti (Dinasti Research, 2025)
This study focuses on the main issues including the proof of girik arrangement in land acquisition disputes. The purpose of this study is to determine how the judge's considerations regarding the status of girik arrangement on evidence of land ownership and the process of proving girik in land disputes in the Tangerang District Court Decision Number 907/Pdt. G/2018/PN Tng. The method used in this study uses a normative legal method with a case approach and a statue approach to analyze various appropriate problems. The findings state that the validity of the arrangement of girik C No. 157 plot 96D covering an area of 2980 m2 in the name of Margawi as proof of land ownership in the Tangerang District Court Decision Number 907/Pdt. G/2018/PN Tng is proven by the history of the land and must go through a land ownership verification process. Initially, girik land was ownership of customary land, so in carrying out girik proof, verification must be carried out by inspection by the local Land Office or the Village Head.